2020
DOI: 10.3892/etm.2020.9405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine combined with etomidate on IL‑17A and S‑100β expression levels in rats with postoperative cognitive dysfunction

Abstract: The present study aimed to explore the effects of dexmedetomidine combined with etomidate on the expression levels of interleukin (IL)-17A and S-100β in rats with postoperative cognitive dysfunction (POCD). A total of 50 SD rats were randomly allocated into the control group, model group, etomidate group (Eto group), dexmedetomidine group (Dex group) and dexmedetomidine combined with etomidate group (Dex-Eto group). Inhalation anesthesia was used in all five groups. Apart from the control group, partial lobect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…It has been confirmed that etomidate mitigates NF-κB activation and pro-inflammatory cytokine production in rat macrophages ( Liu M. et al, 2016 ). Compared with treatment with dexamethasone etomidate, Dex combined with etomidate yields a more satisfactory therapeutic effect in the treatment of older rats with POCD, effectively improving cognitive dysfunction and alleviating stress-related inflammation ( Yu and Xie, 2020 ).…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…It has been confirmed that etomidate mitigates NF-κB activation and pro-inflammatory cytokine production in rat macrophages ( Liu M. et al, 2016 ). Compared with treatment with dexamethasone etomidate, Dex combined with etomidate yields a more satisfactory therapeutic effect in the treatment of older rats with POCD, effectively improving cognitive dysfunction and alleviating stress-related inflammation ( Yu and Xie, 2020 ).…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…POCD is the result of various mechanisms, such as neuroinflammation, oxidative stress, dysfunction of neurotransmitters or their receptors, circadian rhythm disorders, iron overload ( Gögenur et al, 2007 ; Li et al, 2016 ; Netto et al, 2018 ; Luo et al, 2019 ; Wang C. M. et al, 2021 ). At present, the drugs for the prevention and treatment of POCD include non-steroidal anti-inflammatory drugs (parecoxib, acetaminophen, ibuprofen), anesthesia-related drugs (dexmedetomidine, etomidate, oxycodone), ulinastatin, desferrioxamine, antipsychotics, and so on ( Zhou et al, 2019 ; Gan et al, 2020 ; Huang et al, 2020 ; Yu and Xie, 2020 ; Zhao et al, 2020 ; Duan et al, 2021 ). However, there is still a lack of safe and effective ideal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the above results indicate that dexmedetomidine can effectively maintain the balance of cerebral oxygen supply and demand in elderly colorectal cancer surgery. In addition, MBP, NSE, S100β and other indicators are important marker molecules that reflect the damage of nerve cells, and have a certain effect on maintaining the proliferation and differentiation of neurons or glial cells ( 15 ). In this study, the levels of MBP, NSE, and S100β in the observation group were significantly lower than those in the control group, indicating that dexmedetomidine has a certain protective effect on nerve function damage caused by intravenous inhalation and combined anesthesia in elderly patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%